Development of a web-based multidrug-resistant organisms (MDRO) monitoring and transmission tracking system on the basis of microbiology and molecular characteristics. Issue 1 (1st January 2021) - Teh, Cindy Shuan Ju; Lee, Yee Qing; Kong, Zhi Xian; Woon, Jia Jie; Niek, Wen Kiong; Lau, Min Yi; Idris, Nuryana; Ponnampalavanar, Sasheela Sri La Sri; Ho, Peng Foong; Yee Por, Lip
Abstract : Pulsed-field gel electrophoresis (PFGE) remains the tool for transmission and outbreak tracing. However, inter-laboratory comparison of PFGE could not be made due to the lack of a standard for interpretation and congruence profiles assignment. This study aims to overcome the shortcoming of PFGE profiling, as well as human performance in data analysis by developing a web-based tool for monitoring multidrug-resistant organisms (MDRO) and tracking the transmission based on PFGE. A web-based MDRO monitoring and transmission tracking system was developed based on three main subsystems. To build the database, banding patterns of PFGE were converted into string data using the box-based fragmentation method. The data could be visualized based on different categories and the transmission tracing could be achieved by the coexistence of the similar profile. This system could be used for monitoring the genotypic and phenotypic trends of MDRO and to trace potential outbreaks in hospitals.